2020
DOI: 10.4103/jfmpc.jfmpc_38_20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of alcohol use and the interventions needed among adults: A community study in a rural area in South India

Abstract: Background: The health issues and social problems associated with alcohol use are well known. This study seeks to identify the prevalence of alcohol consumption and dependence among alcohol users in a rural area of Trivandrum district. Objectives: To assess the prevalence of alcohol use among adults of Nellanad Panchayat, a rural area in Trivandrum, Kerala, to find out the interventions required among the alcohol users, and to identify persons with harmful and hazardous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This study concluded with the suggestion of health education in 99 (50%), counseling sessions in 74 (37.8%) and de-addiction in 23 (11.7%) individuals based on AUDIT scoring. 23 In a study conducted by Islam et al in 2016, using the NFHS 4 data, after multivariate logistic regression the age, poor education, occupation, religion, alcohol consumption, marital status and socio-economic status were significantly associated with tobacco usage especially amongst the male population. 24 In GATS 2 (2016-2017) India, the prevalence of smokeless tobacco was observed in 31.7%.…”
Section: Resultsmentioning
confidence: 97%
“…This study concluded with the suggestion of health education in 99 (50%), counseling sessions in 74 (37.8%) and de-addiction in 23 (11.7%) individuals based on AUDIT scoring. 23 In a study conducted by Islam et al in 2016, using the NFHS 4 data, after multivariate logistic regression the age, poor education, occupation, religion, alcohol consumption, marital status and socio-economic status were significantly associated with tobacco usage especially amongst the male population. 24 In GATS 2 (2016-2017) India, the prevalence of smokeless tobacco was observed in 31.7%.…”
Section: Resultsmentioning
confidence: 97%
“…13 In a study from south India, 96.9% reported peer pressure while 39% reported mass media to influence their consumption of alcohol. 15 Our study has some limitations. All the youths interviewed in this study were from the rural region of only one ward and hence this finding cannot be generalized.…”
Section: Substance Use Prevalence Among Youthsmentioning
confidence: 89%
“…The pervasive influence of AUD on family dynamics, including but not limited to the disruption of parenting roles, the strain on spousal relationships, and the alteration of child-parent interactions, necessitates a thorough investigation [ 1 , 2 ]. Kerala, characterized by its unique socio-cultural landscape and the highest per capita alcohol consumption in India, provides a critical backdrop for examining the nuanced ways in which wives of individuals with AUD manage parenting [ 3 , 4 ]. This exploration is imperative, given the significant mental health implications for caregivers and the children involved [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%